Updating Clinical Practices to Promote and Protect Human Milk and Breastfeeding in a COVID-19 Era - van Goudoever, Johannes B.; Spatz, Diane L.; Hoban, Rebecca; Dumitriu, Dani; Gyamfi-Bannerman, Cynthia; Berns, Monika; McKechnie, Liz; Davanzo, Riccardo (Frontiers in Pediatrics, 2022)
The COVID-19 pandemic has impacted breastfeeding and lactation globally, with clinical practices implemented early in the pandemic being mostly anti-breastfeeding, e.g. separation of mothers from their infants, and not evidence based. Evidence has emerged reconfirming the value of human milk, the importance of protecting and supporting breastfeeding, especially the initiation of lactation. However, it is clear that COVID-19 has changed the clinical care paradigm around breastfeeding and lactation support and, as such, it is imperative that practices adapt and evolve to maintain the emphasis on lactation support. One key area to target will be to maximize the use of the antenatal period. The early identification of lactation risk factors together with the development of person-centered methods to deliver breastfeeding information and education to parents-to-be will be critical. In addition, the establishment of a hospital culture that values breastfeeding and prioritizes the use of human milk will be integral for the motivation of health care professionals. That culture will also support active management of the initiation of lactation and the development of a 'back-up plan' toolkit to support the mother experiencing lactation difficulties. Post-discharge support will also be crucial with the development of both in-person and virtual lactation support programs, in particular for the immediate post-discharge period to benefit mothers who experience an early discharge process. These measures will allow for a new, adapted framework of practice that acknowledges the current COVID-19 paradigm and maintains the emphasis on the need to protect and support breastfeeding and the use of human milk.